Diagnosis, Therapy and Follow-up Care of Vulvar Cancer and its Precursors. Guideline of the DGGG and DKG (S2k-Level, AWMF Registry Number 015/059, November 2015 - Schnuerch, H. G.; Ackermann, S.; Alt, C. D.; Barinoff, J.; Boeing, C.; Dannecker, C.; Gieseking, F.; Guenthert, A.; Hantschmann, P.; Horn, L. C.; Kuerzl, R.; Mallmann, P.; et al. (Geburtshilfe und Frauenheilkunde, 2016)
Purpose: This is an official guideline, published and coordinated by the Arbeitsgemeinschaft Gynäkologische Onkologie (AGO, Study Group for Gynecologic Oncology) of the Deutsche Krebsgesellschaft (DKG, German Cancer Society) and the Deutsche Gesellschaft für Gynäkologie und Geburtshilfe (DGGG, German Society for Gynecology and Obstetrics). The number of cases with vulvar cancer is on the rise, but because of the former rarity of this condition and the resulting lack of literature with a high level of evidence, in many areas knowledge of the optimal clinical management still lags behind what would be required. This updated guideline aims to disseminate the most recent recommendations, which are much clearer and more individualized, and is intended to create a basis for the assessment and improvement of quality care in hospitals.Methods:This S2k guideline was drafted by members of the AGO Committee on Vulvar and Vaginal Tumors; it was developed and formally completed in accordance with the structured consensus process of the Association of Scientific Medical Societies in Germany (Arbeitsgemeinschaft der Wissenschaftlichen Medizinischen Fachgesellschaften, AWMF).Recommendations:1. The incidence of disease must be taken into consideration. 2. The diagnostic pathway, which is determined by the initial findings, must be followed. 3. The clinical and therapeutic management of vulvar cancer must be done on an individual basis and depends on the stage of disease. 4. The indications for sentinel lymph node biopsy must be evaluated very carefully. 5. Follow-up and treatment for recurrence must be adapted to the individual case.
EVALuna2:33452